2011
DOI: 10.1093/rheumatology/ker315
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of trigger finger: randomized clinical trial comparing the methods of corticosteroid injection, percutaneous release and open surgery

Abstract: The percutaneous and open surgery methods displayed similar effectiveness and proved superior to the conservative CS method regarding the trigger cure and relapse rates. Trial registration. Current Controlled Trials, http://www.controlled-trials.com/, ISRCTN19255926.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
1
20

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 25 publications
2
101
1
20
Order By: Relevance
“…This procedure has demonstrated good results with a low complication rate. [12][13][14][15][16] PR is considered a reasonable surgical option in adults [17][18][19] but is not widely used in children.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has demonstrated good results with a low complication rate. [12][13][14][15][16] PR is considered a reasonable surgical option in adults [17][18][19] but is not widely used in children.…”
Section: Discussionmentioning
confidence: 99%
“…13 A randomized, controlled, clinical trial from 2011 studied the results after open surgery, percutaneous release, and steroid injection (Level of Evidence: Therapeutic, I). 14 The open and percutaneous surgery methods proved similar and superior to injection in terms of cure (100 percent versus 57 percent in the injection group) and relapse rates, with no nerve injuries reported. Although most authors have proceeded to open surgical release of the A1 pulley when percutaneous release has been ineffective, it was recently reported that repeated percutaneous release was successful in 28 of 31 digits following repeat percutaneous release, with no adverse effects.…”
Section: New Developmentsmentioning
confidence: 85%
“…Other studies have demonstrated lower success rates (Shakeel et al 70% [19], Kolind-Sorensenb 67% [3], DalaAli et al 66% [21], Murphy et al 64% [13], Rhoades et al 63% [25], Taras et al 62% [23], Lambert et al 60% [12], Maneerit et al 47% [14]). Sato et al [26] found the trigger cure rate of 57% with single injection and 86% after two injections.…”
Section: Discussionmentioning
confidence: 97%